2013
DOI: 10.1051/epjconf/20134006005
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of magnetocaloric properties of Gd-Ge-Si alloys by alloying with iron

Abstract: Abstract. The influence of annealing of Gd 5 Ge 2 Si 2 Fe x alloys at 1200°C and of alloying with various amount of iron on structure as well as thermal and magnetocaloric properties is investigated. It was found that annealing for 1 to 10 hours improves the entropy change, but reduces the temperature of maximum magnetocaloric effect by up to 50 K. Prolonged annealing of the Gd 5 Ge 2 Si 2 alloy results in the decrease of entropy change due to the reduction of Gd 5 Ge 2 Si 2 phase content. Addition of iron to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…For several years, the chemical composition of the Gd 5 Si 2 Ge 2 has been intensively modified in order to improve magnetocaloric properties. As it was shown in [2,3], the additions such as Al, Cu, Ga, Mn, Co cause an increase in the Curie temperature and imply second order phase transition, which decreases the magnetic entropy change. Hasiak in [4] has shown that small amount of Ni addition leads to decrease of the Curie temperature and slight increase of magnetic entropy change is observed.…”
Section: Introductionmentioning
confidence: 75%
“…For several years, the chemical composition of the Gd 5 Si 2 Ge 2 has been intensively modified in order to improve magnetocaloric properties. As it was shown in [2,3], the additions such as Al, Cu, Ga, Mn, Co cause an increase in the Curie temperature and imply second order phase transition, which decreases the magnetic entropy change. Hasiak in [4] has shown that small amount of Ni addition leads to decrease of the Curie temperature and slight increase of magnetic entropy change is observed.…”
Section: Introductionmentioning
confidence: 75%
“…These alloys are intensively investigated because they exhibit high magnetocaloric effect (MCE), represented by magnetic entropy changed (|ΔS M |), in the vicinity of the Curie point, which is close to the room temperature [ 18 , 19 , 20 ]. It was also shown that the Curie temperature could be changed by the introduction to master alloys additives such as Co, Fe, Zr, Pr, Ni or Ce [ 9 , 16 , 18 , 21 , 22 ]. High MCE in these alloys allows them to be used in cooling technology, for example, in the production of ecofriendly magnetic refrigerators [ 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%